BANK MONITORING AS AN EXTERNAL GOVERNANCE MECHANISM AND THE BORROWERS’ FIRM VALUE - Alexandra Ryan Ahmad Dina; Ancella Anitawati Hermawan (Bina Nusantara University, 2013)
The objective of this research is to examine the effect of bank monitoring as an alternative of corporate governance mechanisms on the borrowers’ firm value. The strengths of bank monitoring on the borrowers are measured based on the magnitude of the bank loan, the size of the loan from banks with high monitoring quality, the length of a bank loan outstanding period, and the number of lenders. The research hypotheses were tested using multiple regression model with a sample of 230 companies listed in Indonesia Stock Exchange during 2009. The empirical results show that only the size of the loan from banks with high monitoring quality and the number of lenders significantly influences the borrowers’ firm value. These findings imply that only banks with high monitoring quality could play an important role in the corporate governance and therefore increasing the firm value by their monitoring function. Furthermore, bank monitoring is less effective if a company borrows from many banks, and therefore decreasing the firm value.